Self-regulation and maternal mental health interactions from birth to age seven: Mother- or child-driven effects - Walker, Sue; Williams, Kate; Berthelsen, Donna; Nicholson, Jan M (My University, 2013)
Children’s self-regulation skills develop through dynamic, transactional processes between parent and child. There is substantial existing evidence for the influence of maternal mental health on children’s general development, but limited studies on the longitudinal relationships between children’s early self-regulatory capacity and maternal mental health. Further, although transactional models of child development hypothesise that child-driven effects as well as mother-driven effects are likely, there are limited empirical findings to support this view. This study used data for 2880 children, participating in The Longitudinal Study of Australian Children (LSAC) Baby cohort. Sleep regulation and temperamental reactivity and persistence from birth to age five were used as self-regulation indicators in a series of longitudinal structural equation models (SEMs). The mother-driven and child-driven models fitted the data well. Mothers with a history of depression were more likely to have infants with poor sleep and emotional regulation at Wave 1. Mothers with poorer mental health at Wave 1 were also more likely to have children with poorer sleep, emotional and cognitive regulation two years later. Evidence was also found to support child-driven effects. Even when mother’s prior mental health was accounted for, children with poorer emotional regulation at Wave 2 were associated with poorer maternal mental health two years later, and poor sleep and emotional regulation in children at Wave 3 also contributed small but unique variance to maternal mental health at Wave 4. These findings contribute to a greater understanding of the mother-child system and highlight the importance of targeting maternal mental health in preventive strategies.
Keywords: Families -- Mothers; Child Development -- Sleep; Child Development -- Behaviour; Health -- Mental; Childhood and child development; Families and relationships; Health and wellbeing; Families; Health; Child Development; Behaviour; Mental; Mothers; Sleep; Families and relationships; Childhood and child development; Health and wellbeing